ANALISIS PENILAIAN PROPERTI BERUPA RUMAH TINGGAL DI PERUMAHAN CITRALAND CITY SAMARINDA PADA KJPP. AKSA, NELSON & REKAN - -, Dina Mustika (EKONOMIA, 2017)
Assessment is one service sector that can play an important role in shaping the economic value of assets and potential wealth. Value estimation is a realistic indication and can be sold at any given time. The purpose of this study is to determine and analyze the market value of residential property in Citraland City housing in Samarinda in 2016. Broadly speaking the problem is formulated as follows, whether the market value of residential property in Citraland City housing in Samarinda in 2016 has increased based on data approach Market and cost approach. The basic theory in this study is financial accounting that focuses on asset valuation. The hypothesis proposed is that the market value of residential property in Citraland City housing in Samarinda in 2016 has increased based on the approach of market data and cost approach. Analyzer used in this research is method of approach of market data and cost approach method that is by doing comparison and cost calculation. The results of analysis and discussion of the market value of housing in Citraland City Samarinda housing in 2016 amounted to Rp. 2,277,509,028, where the market value of land amounted to Rp.5.550.000, - / m² and the market value of the building after experiencing physical depreciation to Rp. 4.953.677, - / m². The cost of replacing the new building is estimated at Rp. 5504.086, - / m². Based on the results of the analysis, the residential house in Citraland City Samarinda housing increased market value in 2016 seen from the method of market data approach and cost approach that shows the balance of supply of similar properties, the hypothesis accepted.